Postgraduate students’ perception of Massive Open Online Courses (MOOCs) in enhancing their learning experience - Abd Majid, Faizah (Australian International Academic Centre PTY.LTD., 2019)
MOOCs first became a phenomenon in the higher education landscape in 2008. Ever since, various researches have been conducted to explore the potential of MOOCs as an alternative in the learning and teaching process, and the way forward in delivering the courses effectively. Despite the growing interest in MOOCs applicability in higher education, very little is known about how postgraduate students perceive the use of MOOCs in their programme. Postgraduate students are synonymous with the concept of adult learners. One of the characteristics of adult learners is their motivation, which is driven by intrinsic and instrumental factors. As past research have concentrated on the undergraduates, this paper uncovers the postgraduates’ perceptions of MOOCs. A total of 51 respondents took part in a survey conducted in one of the Malaysian public universities. Quantitative data yielded findings similar to past research findings. However, what is new is the need for MOOC providers to cater to the needs of the postgraduate students who are adult learners particularly in determining the following; MOOCs’ attributes, learning process and learning outcomes. It is expected that the postgraduate students, their educators and the MOOC developers would find the findings helpful